Characteristics, risk factors and treatment reality in livedoid vasculopathy – a multicentre analysis. (14th May 2019) - Weishaupt, C.; Strölin, A.; Kahle, B.; Kreuter, A.; Schneider, S. W.; Gerss, J.; Eveslage, M.; Drabik, A.; Goerge, T.
Abstract: Background: Livedoid vasculopathy (LV) is a rare cutaneous thrombotic disease. It is characterized by occlusion of dermal vessels resulting in livedo racemosa, ulceration and atrophie blanche. Clear guidelines for diagnosis and treatment are missing. Objective: The purpose of this study was to better characterize epidemiology, clinical appearance and treatment reality of LV in a well‐defined patient cohort. Methods: The cohort was allocated within a prospective, multicentre, phase IIa trial that investigated the effect of rivaroxaban in LV. Results: Analysis of 27 patients revealed that LV patients had an increased Body Mass Index (BMI; 11/27), hypertension (19/27) and increased levels of lipoprotein (a) (5/12) and homocysteine (10/12) in the blood. The female‐to‐male ratio was 2.1 : 1, and the median age was 53.0 years [interquartile range (IQR) 40.5–68]. Investigation of the clinical appearance found that 82% of patients had livedo racemosa, and the ankle region was most likely to be affected by ulceration (56–70%). The analysis of patient treatment history showed that heparin was most effective (12/17), while anti‐inflammatory regimens were, although often used (17/24), not effective (0/17). Conclusion: We add clinical clues for a data supported diagnosis of LV, and we provide evidence that anticoagulants should be administered in monotherapy first line (EudraCT number 2012‐000108‐13‐DE). Abstract : Linked Commentary: D. Lipsker. J Eur Acad Dermatol Venereol 2019; 33 : 1627–1628. https://doi.org/10.1111/jdv.15830 .